Modern trends of digitalization of innovation process - E. N. Bykovskaya; G. P. Kharchilava; Yu. N. Kafiyatullina (Управление)
The purpose of this article is to identify modern aspects and problem areas in the field of digitalization of the innovation process. Digital technologies are becoming an increasingly important component of the various functional areas of the organization, and in some situations, the success of a business project. Digital technologies open great prospects for the conduct of various kinds of business, allow organizing international cooperation with minimal costs, thus accelerating globalization, stimulating development and expanding the boundaries of the world economic space.The wide use of digital technologies allows for the networking between the participants in the innovation process, ensures the formation of competitive advantages, optimizes the use of economic and other types of resources, and also enhances coordination and communication. Unfortunately, in Russia the level of application of digital organizations, in comparison with foreign organizations of developed countries, remains at a low level. In our country, the need for the use of information technology has matured long ago, but only since May 2017 the relevant regulatory documents have been issued that encourage organizations to actively digitize all areas and functional areas of their activities. Modern information technologies are characterized by high computing power, they take control of the organization, production, creation of innovations to a fundamentally different quality level.Currently, the success of competition is determined by the ability of organizations to quickly implement and commercialize innovations and obtain superprofits, in this regard it seems relevant to explore the possibilities of digital solutions and technologies for the effective management and management of innovation.The article analyzes the current state of the information technology industry and the information and communication technologies industry, on the basis of which the problems of the industry development have been identified, and proposals have been developed to use digital products to stimulate the innovation process.